2020
DOI: 10.15414/raae.2020.23.01.65-72
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Profitability of Poultry Egg Production in Southwest Nigeria. An Application of Quantile Regression

Abstract: This study investigated the key factors affecting the profitability of poultry egg production in Southwest, Nigeria. A multi-stage sampling procedure was employed to select 360 egg farmers using a structured questionnaire. Data collected were analysed using descriptive and inferential statistics. Descriptive statistics showed that the mean age of egg farmers was 45 years. Majority (68.3%) of the farmers were male households. Over half (57.8%) of the farmers had tertiary school education and majority (85.0%) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Figures 3a -3f depict the visualisation of the forecast (for the preferred model ARIMA (3,1,0)) of the price of a dozen mediumsized eggs for the 6 geo-political zones in the country. The rising cost of eggs can be attributed to the high cost of inputs (e. g feeds) which is a major challenge in poultry business as feed purchase alone can be as high as 70% of the cost of production leading to a drastic decrease in the number of commercial poultry farmers, and even more the small-scale ones who could not cope with the production of eggs at high cost (Johnson et al, 2019). Sustainable food security should be the desire of any nation, including Nigeria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 3a -3f depict the visualisation of the forecast (for the preferred model ARIMA (3,1,0)) of the price of a dozen mediumsized eggs for the 6 geo-political zones in the country. The rising cost of eggs can be attributed to the high cost of inputs (e. g feeds) which is a major challenge in poultry business as feed purchase alone can be as high as 70% of the cost of production leading to a drastic decrease in the number of commercial poultry farmers, and even more the small-scale ones who could not cope with the production of eggs at high cost (Johnson et al, 2019). Sustainable food security should be the desire of any nation, including Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the nutrient -rich nature of eggs, government should strive and engage stakeholders with policies to improve and encourage the production of eggs nationwide. Though the Nigerian government keeps attempting to abate the problem of input demand in poultry industry through programmes such as Micro-Credit Scheme for Livestock Production, Community-Based Agricultural and Rural Development Project, National Egg Production (NEGPRO) and African Chicken Genetic Gain in Nigeria (ACGG-NG) (Johnson et al, 2019); more still needs to be done to keep this very important protein -rich meal in the menu of the average Nigerian. et al, 2020), egg production can continue to be a lucrative business for both poultry farmers as well as investors, if the government make more concerted efforts to keep the price affordable.…”
Section: Resultsmentioning
confidence: 99%
“…The age was negatively related with the income in all the quantiles but significant at the T.25 quantile, being the highest magnitude in terms of the coefficient. The issue of age in relation with income has been viewed from two perspectives: (i) some researchers reported that the increase in age would lead to decrease in productivity and thereby reduce the income of the farmers [31,37,71]; and (ii) some researchers as well linked age with experience, and believed that aged farmers would have gathered adequate knowledge and skills over the years on how to improve productivity and income [33,38,72,73]. The present study disagreed with the later school of thought because age is not a prerequisite for engaging in the poultry business.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in the literature examined outcome continuous variables such as farm income, using Ordinary Least Squares (OLS) [23,[34][35][36]. Although [37,38] also employed quantile regression to examine the profitability of cocoa marketers and egg poultry farmers, respectively, this study is different by modelling HMPs and behavioral factors into the heterogeneity of both layers and broiler poultry farmers' income. Since the adoption and utilization of HMPs is indispensable in the poultry enterprise, understanding its effect on the farm's performance will be a policy framework to promote sustainable development in the livestock industry.…”
Section: Introductionmentioning
confidence: 99%
“…Egg production represents an important segment of the world food industry. However Seasonal variation affects the demand for eggs [1]. As a result, there are periods of extended egg glut and huge number of eggs are stored.…”
mentioning
confidence: 99%